Efflux genes and active efflux activity detection in of methicillin-resistant Staphylococcus aureus (MRSA). - Saiful, Azmi Johari; Mohtar, Mastura; Zarizal, Suhaili; Mazurah, Mohamed Isa; Shuhaimi, Mustafa; Ali, Abdul Manaf (Wiley-Blackwell, 2008)
Efflux-mediated resistance has been recognized as an important contributor of antibiotic resistance in bacteria, especially in methicillin-resistant Staphylococcus aureus (MRSA) isolates. This study was carried out to detect and analyze efflux genes (norA and mdeA) and active efflux activity in a collection of Malaysian MRSA and methicillin-sensitive S. aureus (MSSA) clinical isolates. Nineteen isolates including three ATCC S. aureus reference strains were subjected to PCR detection and DNA sequence analysis for norA and mdeA and active efflux detection using modified minimum inhibitory concentration (MIC) assay. From the 19 isolates, 18 isolates harboured the mdeA gene while 16 isolates contained norA gene. DNA sequence analysis reveals 98–100% correlation between the PCR product and the published DNA sequences in GenBank. In addition, 16 isolates exhibited active efflux activity using the ethidium bromide (EtBr)- reserpine combination MIC assay. To our knowledge, this is the first report on the detection of efflux genes and active efflux activity amongst Malaysian clinical isolates of MRSA/MSSA. Detection of active efflux activity may explain the previous report on efflux-mediated drug resistance profile amongst the local clinical isolates.